Experiences of self-monitoring in self-directed weight loss and weight loss maintenance: systematic review of qualitative studies - Hartmann-Boyce, J; Boylan, AM; Jebb, SA; Aveyard, P (SAGE Publications, 2018)
The experience and role of self-monitoring in self-directed weight loss attempts may be distinctly different from that within formal interventions, and has yet to be fully explored. We systematically reviewed qualitative studies to examine experiences of self-monitoring as an aid to self-directed weight loss. Thematic synthesis was used to construct descriptive and analytical themes from the available data. 22 studies (681 participants) were included, in which the uses of self-monitoring ranged from an aid to increase adherence to a tool for facilitating analysis. Self-monitoring also influenced and was influenced by self-perception and emotions. Feelings of shame were linked with abandonment of efforts. Findings highlight the centrality of interpretation of self-monitored data, the implications this interpretation has on sense of self, and the impact of broader discourses. Explicitly framing self-monitoring as a positive tool with which to aid analysis may encourage helpful use of this technique.